Regulatory and Legal Enforcement of Cyber Security in Countries of the European Union: The Experience of Germany and France - Kavyn, Sviatoslav; Bratsuk, Ivan; Lytvynenko, Anatoliy (Teisė, 2021)
This article is devoted to the study of information security in the EU member states, in particular Germany and France, in the context of the analysis of their national legislation, state, national programs and regulations. Particular attention is paid to the study of the features of regulatory and legal security of information security of Germany and France in the context of the study of their national legislation in terms of economic security as an inherent component of national security. In the course of this study the peculiarities of the functioning of the institutional and legal mechanism of cyber defense in the context of the multi-vector system of international security and legal regulation of international cooperation are analyzed. The article substantiates the expediency of developing an integrated, coordinated information policy of the EU member states in order to unify approaches to information security. At the same time, the current realities of European Union policy require comprehensive research in the context of ensuring national interests, developing effective mechanisms for protecting the information space, and legal mechanisms for shaping the economic system as a strategic factor of national security. Accordingly, the approaches to information security adopted in the European Union are currently not unified due to the geopolitical specifics of the EU’s countries. Therefore, the research, evaluation, and implementation of the positive experience of Germany and France in this area, according to the authors, is important in building the information security system of the European Union in the context of reliable protection against cyber threats.